Strategi Rekrutmen Dosen Berbasis Matrik S.W.O.T. di Institut Agama Islam Al Muhammad Cepu - Kharisma Puspita Sari; Mamiek Slamet (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2024)
High institution needed the management of employment resources that were suitable, fair, and selective. However, the educational workers from private institution frequently considered as low quality workers because they could not be competitive with others. Al Muhammad Cepu High Institute has a fixed strategies for the recruitment of lecturers from Assistant Professor (AA/Asisten Ahli) up to Full Professor (Guru Besar/GB). In this study, the current researchers aimed to describe strategies in recruiting lecturers. Those strategies was reached based on the S.W.O.T. matrix analysis with the internal and external factors. This was descriptive research by completing the collaborative approach between qualitative and quantitative. Qualitative data were identifications of internal external factors and synchronization of any norm and applicable rules related to lecturer’s recruitment. Quantitative data were tabulation of IFAS AND EFAS factors. Next, the writers have found two strategies for recruiting functional-level lecturers that were; 1) open-ended recruitment, and 2) closed-ended recruitment. Moreover, from the current employment data and those applicable recruitment systems, the researchers processed the findings by using the S.W.O.T. approach. This process occurred in some steps like a)identifying internal and external factors, and b)composing IFAS (Internal Factor Analysis Strategy) and EFAS (External Factor Analysis Strategy), c) confirming the statistical rate starts from 0,00 up to 1,00, d) taking the level from the number of 1,00 up to 4,00, and e) making quadrant matrix and relativity ratio, and 4)explain the challenges, obstacles, and opportunities.